BAKTERI PATOGEN PENYEBAB PEN YAKIT MULUT MERAH PADA IKAN KERAPU TIKUS (Cromileptes altivelis PATHOGENIC BACTERIA CAUSING RED MOUTH DISEASE INGRACE CALLY (Cromileptes altivelis - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRACT: Grouper, grace cally (Cromileptes altivelis) is one of the fisheries commodities that gains economically importance as both consumable fish and as ornamental fish. So far, disease problems is still causing mass mortality up to 100%. Bacterial infection is suspected of being agents responsible for mass mortality. Diseased fish usually has gross signs such as red mouth, reddish colour of the body, fin rot and swelling stomach followed by sudden death. A study was conducted to determine agent(s) causing the disease. Bacteria were isolatpd from mouth ulcer, liver, kidney and gut. Purification and identification resulting 7 bacteria associated with the disease, four of them belong to genera of Vibrio. Two spesies of Vibrio which are V. alginolyticus and V. anguillarum were then infected intraperitoneally (IP) into 4.5 g fishes for pathogenicity test. Result of the experiment for pathogenicity test showed that V. alginolyticus was more pathogen than that of V. anguillarum. At the density of 108'88 CFU/fish, a LD50 was resulted from 96 hours of exposure of V. alginolyticus to fish, while up to 108 CFU/fish of V. anguillarum only caused 20% mortality.